Study Influence of Substrate Temperature on Optical Properties of CdS Thin Films Prepared by Chemical Spray pyrolysis - Saleh, Karrar Mahdi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
This study aims to prepare Cadmium Sulphide (CdS) thin films using thermal Chemical Spray Pyrolysis (CSP) on glass of different temperatures substrate from cadmium nitrate solution. Constant thickness was (430 Â± 20 nm) and the effect of substrate temperature on the optical properties of prepared thin films. Optical properties have been studied from transmittance and absorbance spectral within wavelengths range (360 - 900 nm). The results show that all the prepared films have a direct electron transitions and optical energy gap between (2.31-2.44 eV). They also show that the transmittance and optical energy gap of films prepared from nitrate solution increase with increasing of substrate temperature, then transmittance start downward with the continued increase in temperature (400, 450) oC.